Comparative analyses of two mathematical models obtained from two modeling techniques for prediction of compressive strength of sand-laterite blocks - Elizabeth, Okere Chinenye (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Scheffe’s and Osadebe’s modeling techniques were used in formulating two mathematical models for the prediction of compressive strength of sand laterite blocks. The models were tested for adequacy using statistical tools. Comparative analyses were made on the results of predictions from the two models. The student’s t-test statistics proved that there is no significant difference between the predicted results of the two models at an α-level of 0.5. The percentage difference between the two model results ranges from a minimum of 0.25% to a maximum of 6.66% which is also insignificant. These comparisons show that both models are adequate and any of them can be used for prediction of the compressive strength of sand -laterite blocks given the mix ratios or vice versa.